INTERPRETASI REMAJA PEREMPUAN KOTA DENPASAR TERHADAP FENOMENA CATCALLING - Paramita Sari, Ida Ayu Indah; Zuryani, Nazrina; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI: SOROT, 2021)
The phenomenon of catcalling is a form of calling in the form of whistling, throwing seductive words at the victim. Not only the temptation that the victim gets in this phenomenon, but the victim also gets an unpleasant attitude by the perpetrator after the perpetrator makes the temptation. The approach used in this research is a qualitative approach with the type of exploratory research. The theory used is the theory of action in George Herbert Mead's symbolic interactionism to examine the interpretation of the female teenagers in Denpasar City who are victims of the catcalling phenomenon. This study also discusses the psychological and social impacts experienced by victims of catcalling. The catcalling phenomenon occurs when the victim is in public places and the victim's housing area. Key words:  Catcalling, Interpretation, Teenage girl